Last active
April 12, 2018 14:32
-
-
Save shhyou/5df3f217c129c52d6a9ed9deb9566fa8 to your computer and use it in GitHub Desktop.
This file contains hidden or bidirectional Unicode text that may be interpreted or compiled differently than what appears below. To review, open the file in an editor that reveals hidden Unicode characters.
Learn more about bidirectional Unicode characters
#!/usr/bin/env python3 | |
# 歸納法樣板 | |
class InductionProof: | |
def induction(self, tabs, n): | |
if n == 1: | |
return tabs + self.base_case.replace("n", str(n)) | |
else: | |
m = n-1 | |
inductive_hypothesis = "\n".join(tabs + s for s in self.induction(tabs, m).split("\n")) | |
proof = self.inductive_case.replace("n", str(n)).replace("m", str(m)) | |
proof = proof.replace("由歸納假設", inductive_hypothesis) | |
proof_lines = proof.split("\n") | |
proof_lines = \ | |
["/ " + proof_lines[0]] + \ | |
["| " + s for s in proof_lines[1:-1]] + \ | |
["\\ " + proof_lines[-1]] | |
return "\n".join(proof_lines) | |
def __init__(self, base_case, inductive_case): | |
self.base_case = base_case | |
self.inductive_case = inductive_case | |
def __call__(self, n): | |
return self.induction(" ", n) + "\n" | |
# 證明 1+2+...+n = n(n+1)/2 | |
sum_k = InductionProof( \ | |
# 當 n = 1 | |
base_case = "n = n*(n+1)/2, 式子成立", \ | |
# 當 n = m+1 | |
inductive_case = """ | |
1+...+n | |
= 1+...+m+(m+1) | |
= (1+...+m)+(m+1) | |
由歸納假設 | |
= m(m+1)/2 + (m+1) | |
= (m+1)(m/2 + 1) | |
= (m+1)(m+2)/2 | |
= (m+1)((m+1)+1)/2 | |
= n(n+1)/2 | |
""") | |
print(sum_k(7)) | |
""" | |
$ python3 generator_for_weak_nat_induction.py | |
/ | |
| 1+...+7 | |
| = 1+...+6+(6+1) | |
| = (1+...+6)+(6+1) | |
| / | |
| | 1+...+6 | |
| | = 1+...+5+(5+1) | |
| | = (1+...+5)+(5+1) | |
| | / | |
| | | 1+...+5 | |
| | | = 1+...+4+(4+1) | |
| | | = (1+...+4)+(4+1) | |
| | | / | |
| | | | 1+...+4 | |
| | | | = 1+...+3+(3+1) | |
| | | | = (1+...+3)+(3+1) | |
| | | | / | |
| | | | | 1+...+3 | |
| | | | | = 1+...+2+(2+1) | |
| | | | | = (1+...+2)+(2+1) | |
| | | | | / | |
| | | | | | 1+...+2 | |
| | | | | | = 1+...+1+(1+1) | |
| | | | | | = (1+...+1)+(1+1) | |
| | | | | | 1 = 1*(1+1)/2, 式子成立 | |
| | | | | | = 1(1+1)/2 + (1+1) | |
| | | | | | = (1+1)(1/2 + 1) | |
| | | | | | = (1+1)(1+2)/2 | |
| | | | | | = (1+1)((1+1)+1)/2 | |
| | | | | | = 2(2+1)/2 | |
| | | | | \ | |
| | | | | = 2(2+1)/2 + (2+1) | |
| | | | | = (2+1)(2/2 + 1) | |
| | | | | = (2+1)(2+2)/2 | |
| | | | | = (2+1)((2+1)+1)/2 | |
| | | | | = 3(3+1)/2 | |
| | | | \ | |
| | | | = 3(3+1)/2 + (3+1) | |
| | | | = (3+1)(3/2 + 1) | |
| | | | = (3+1)(3+2)/2 | |
| | | | = (3+1)((3+1)+1)/2 | |
| | | | = 4(4+1)/2 | |
| | | \ | |
| | | = 4(4+1)/2 + (4+1) | |
| | | = (4+1)(4/2 + 1) | |
| | | = (4+1)(4+2)/2 | |
| | | = (4+1)((4+1)+1)/2 | |
| | | = 5(5+1)/2 | |
| | \ | |
| | = 5(5+1)/2 + (5+1) | |
| | = (5+1)(5/2 + 1) | |
| | = (5+1)(5+2)/2 | |
| | = (5+1)((5+1)+1)/2 | |
| | = 6(6+1)/2 | |
| \ | |
| = 6(6+1)/2 + (6+1) | |
| = (6+1)(6/2 + 1) | |
| = (6+1)(6+2)/2 | |
| = (6+1)((6+1)+1)/2 | |
| = 7(7+1)/2 | |
\ | |
""" |
This file contains hidden or bidirectional Unicode text that may be interpreted or compiled differently than what appears below. To review, open the file in an editor that reveals hidden Unicode characters.
Learn more about bidirectional Unicode characters
#!/usr/bin/env python3 | |
# 證明 1+2+...+n = n(n+1)/2 | |
def induction(tabs,n): | |
if n == 1: # Base case: 當 n = 1 | |
print("%s%d*(%d+1)/2 = %d, 成立." # 1*(1+1)/2 = 1, 式子成立 | |
% (tabs,n,n,n)) | |
else: | |
m = n-1 # Inductive case: 當 n = m+1 | |
print("%s/ 1+2+...+%d+(%d+1)"%(tabs,m,m)) # / 1+2+...+m+(m+1) | |
print("%s| = (1+2+...+%d)+(%d+1)"%(tabs,m,m)) # | = (1+2+...+m)+(m+1) | |
induction(tabs+"| ",m) # | 由歸納假設, (1+2+...+m)=m(m+1)/2 | |
print("%s| = %d*(%d+1)/2 +(%d+1)"%(tabs,m,m,m)) # | = m*(m+1)/2 + (m+1) | |
print("%s| = (%d/2 + 1)(%d+1)"%(tabs,m,m)) # | = (m/2 + 1)(m+1) | |
print("%s| = (%d+2)(%d+1)/2"%(tabs,m,m)) # | = (m+2)(m+1)/2 | |
print("%s\\ = (%d+1)((%d+1)+1)/2"%(tabs,m,m)) # \ = (m+1)((m+1)+1)/2 也成立 | |
induction("",7) | |
""" | |
$ python3 induction.py | |
/ 1+2+...+6+(6+1) | |
| = (1+2+...+6)+(6+1) | |
| / 1+2+...+5+(5+1) | |
| | = (1+2+...+5)+(5+1) | |
| | / 1+2+...+4+(4+1) | |
| | | = (1+2+...+4)+(4+1) | |
| | | / 1+2+...+3+(3+1) | |
| | | | = (1+2+...+3)+(3+1) | |
| | | | / 1+2+...+2+(2+1) | |
| | | | | = (1+2+...+2)+(2+1) | |
| | | | | / 1+2+...+1+(1+1) | |
| | | | | | = (1+2+...+1)+(1+1) | |
| | | | | | 1*(1+1)/2 = 1, 成立. | |
| | | | | | = 1*(1+1)/2 +(1+1) | |
| | | | | | = (1/2 + 1)(1+1) | |
| | | | | | = (1+2)(1+1)/2 | |
| | | | | \ = (1+1)((1+1)+1)/2 | |
| | | | | = 2*(2+1)/2 +(2+1) | |
| | | | | = (2/2 + 1)(2+1) | |
| | | | | = (2+2)(2+1)/2 | |
| | | | \ = (2+1)((2+1)+1)/2 | |
| | | | = 3*(3+1)/2 +(3+1) | |
| | | | = (3/2 + 1)(3+1) | |
| | | | = (3+2)(3+1)/2 | |
| | | \ = (3+1)((3+1)+1)/2 | |
| | | = 4*(4+1)/2 +(4+1) | |
| | | = (4/2 + 1)(4+1) | |
| | | = (4+2)(4+1)/2 | |
| | \ = (4+1)((4+1)+1)/2 | |
| | = 5*(5+1)/2 +(5+1) | |
| | = (5/2 + 1)(5+1) | |
| | = (5+2)(5+1)/2 | |
| \ = (5+1)((5+1)+1)/2 | |
| = 6*(6+1)/2 +(6+1) | |
| = (6/2 + 1)(6+1) | |
| = (6+2)(6+1)/2 | |
\ = (6+1)((6+1)+1)/2 | |
""" |
Sign up for free
to join this conversation on GitHub.
Already have an account?
Sign in to comment